2019
DOI: 10.31014/aior.1992.02.04.168
|View full text |Cite
|
Sign up to set email alerts
|

Joint Products CVP Analysis – Time for Methodical Review

Abstract: This paper presents an Income Statement teaching approach for Cost-Volume-Profit (CVP) analysis by using a company's CVP Model that is intuitive and student-friendly. This approach would help students learn about CVP analysis and reduces their memorization of equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…In the context of multiproduct CVP analysis applications, Enyi [14] examines the efficacy of the Weighted Contribution Margin (WCM) with the Reversed Contribution Margin Ratio (RCMR). The WCM lacks analytical efficiency and generates suboptimal product mix because it ignores the inverse relationship between a product's contribution margin ratio (CMR) and its break-even point (BEP).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of multiproduct CVP analysis applications, Enyi [14] examines the efficacy of the Weighted Contribution Margin (WCM) with the Reversed Contribution Margin Ratio (RCMR). The WCM lacks analytical efficiency and generates suboptimal product mix because it ignores the inverse relationship between a product's contribution margin ratio (CMR) and its break-even point (BEP).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the decision under study requires the evaluation of profitability as a function of output, cost-volume-profit (CVP) analysis is an attractive decision tool to use, since it enables managers to make decisions under business conditions where costs, revenue, and volume are changing (see for example [14][15][16]). For situations involving a single product, decision makers can use CVP to determine the sales volume needed to achieve a targeted profit when sales price, variable cost, or fixed cost change.…”
Section: Introductionmentioning
confidence: 99%
“…Lulaj [26] showed how much cost-volume-profit analysis is used for planning and making decisions in business. Enyi [27] compared the effectiveness of Weighted-Contribution-Margin (WCM) and Reversed-Contribution-Margin-Ratio (RCMR) in multi product cost-volume-profit analysis applications. Nagar et al [28] concluded that government economic policy under uncerainity is an important componet of the firm's information enviroments and manger's volunatary decisions.…”
Section: Cost Price and Volume Properties In C-v-p Analysismentioning
confidence: 99%
“…Lulaj and Isaneni [26] showed how much cost-volume-profit analysis is used for planning and making decisions in business. Enyi [27] compared the effectiveness of Weighted-Contribution-Margin (WCM) and Reversed-Contribution-Margin-Ratio (RCMR) in multi product cost-volume-profit analysis applications. Nagar et al [28] concluded that government economic policy under uncertainty is an important component of the firm's information environments and manger's voluntary decisions.…”
Section: Cost Price and Volume Properties In C-v-p Analysismentioning
confidence: 99%